Daily Peak Expiratory Flow Rate and Disease Instability in Chronic Obstructive Pulmonary Disease - So, Jennifer Y. (Chronic Obstr Pulm Dis, 2015)
Rationale: Chronic obstructive pulmonary disease, (COPD) is a major cause of morbidity and mortality in the United States. Peak expiratory flow rate (PEFR) monitoring could provide a daily objective measurement of lung function in COPD patients at home. We hypothesized that individuals with greater variability in daily PEFR would signal an unstable patient population with worse outcomes. Methods: This was a retrospective analysis of prospectively collected data using an electronic diary to record daily PEFR and symptoms in severe and very severe COPD patients. Rates of PEFR change were used to characterize patients into stable and unstable groups determined by the distribution of slopes. Exacerbation-free days, time to first hospitalization, hospitalization rate, length of hospitalization, and all-cause mortality were assessed. Results: A total of 104 severe and very severe COPD patients met entry criteria, and were observed for 37,702 patient-days. There were no significant differences in baseline symptoms, demographics, forced expiratory volume in 1 second (FEV(1)) or comorbidities between stable versus unstable groups. The unstable group had 34.7 less exacerbation-free days and significantly shorter 6 minute walk distances (6MWD) (227.1 versus 270.7 meters, p=0.031), shorter time to first hospitalization (163 versus 286 days, p=0.017), more frequent hospitalizations (2.6 versus 1.7 per year, p=0.032) and higher all-cause mortality (10.8 versus 5.1%, p= 0.04). Conclusion: Patients with severe to very severe COPD with greater changes in PEFR have shorter 6MWD, reduced time to first hospitalization, more frequent hospitalizations, and higher all-cause mortality despite similar demographic, spirometric and comorbid parameters at baseline. Daily peak flow monitoring can be a useful tool in identifying COPD patients predisposed to worse outcomes.